Measurement and characterization method of cement paste pore structure based on X-CT and low-field nuclear magnetism combination
By surface modification of nanocellulose and combining X-CT and low-field nuclear magnetic technology, the poor dispersion and degradability of nanocellulose in cement-based materials are solved, and the effect of improving the mechanical properties and durability of the materials is achieved.
Patent Information
- Application Number
- CN202411911598.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-21
AI Technical Summary
The prior art is difficult to effectively solve the impact of poor dispersion and degradability of nanocellulose in cement-based materials on material properties, affecting the uniformity and durability of the material.
Nanocellulose is treated through surface modification technology, and physical, chemical and mechanical methods are used to improve its dispersion and reactivity in cement-based materials, and porosity research is conducted in combination with X-CT and low-field nuclear magnetic technology.
The good dispersion of nanocellulose in cement-based materials is achieved, the mechanical properties and durability of the material are improved, and the working performance of the material is improved by optimizing the pore structure.
Smart Images

Figure CN119666906A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement-based material testing and analysis, and in particular to a cement slurry porosity research technology using X-CT and low-field nuclear magnetic resonance. Background Art
[0002] In modern society, the demand for high-performance materials is growing, which has promoted the rapid development of the field of materials science. Among them, nanomaterials have shown great application potential in many fields due to their unique physical and chemical properties, and have therefore received extensive attention from researchers and industry in recent years. However, the development of nanomaterials also faces some challenges, such as high production costs and unsatisfactory ecological benefits, which limit their widespread application.
[0003] In this context, nanocellulose (CNF), as a nanomaterial derived from plants, has become a hot topic of research due to its renewable and environmentally friendly characteristics. CNF is a natural polymer material extracted from plant cell walls, which has excellent mechanical properties, optical properties and thermal stability. More importantly, CNF has a good strengthening and toughening effect on cement-based composites, which can improve the mechanical properties and durability of the material.
[0004] However, there are also some problems in the application of CNF. First, CNF is degradable, which limits its service life in certain specific environments. Second, CNF has poor dispersibility in cement-based materials, which affects the uniformity and final performance of the material. In addition, the addition of CNF may affect the durability of cement, such as impermeability, freeze-thaw resistance, and carbonization resistance.
[0005] In order to solve these problems, we tried to modify the surface of CNF through various dispersion methods to improve its dispersibility and reactivity in cement-based materials. Through surface modification, the compatibility of CNF with cement-based materials can be improved, and its dispersibility in the material can be improved, so as to better play its reinforcing and toughening role. In addition, surface modification can also improve the stability of CNF and reduce the impact of its degradability on material properties.
[0006] In the process of preparing modified CNF, we adopted a variety of methods, such as physical, chemical and mechanical methods, to achieve effective regulation of CNF surface properties. Physical methods mainly include ultrasonic dispersion, high shear dispersion, etc., which destroy the aggregates of CNF through mechanical force and improve its dispersibility in cement-based materials. The chemical method mainly introduces hydrophilic groups or hydrophobic groups on the surface of CNF through polycarboxylic acid high-efficiency water reducer PCE and surfactant CTAB to improve its compatibility with cement-based materials. The mechanical method is to disperse CNF under the action of mechanical force through magnetic stirring, ultrasonic bath and high-intensity ultrasonic treatment.
[0007] The modified CNF prepared by these methods has high reactivity and good dispersibility, and can be effectively incorporated into cement-based materials. The addition of these nanomaterials can significantly improve the pore structure of cement-based materials. The pore size distribution of cement-based materials is very wide, such as gel pores (0.5-10nm), small capillary pores (10-50nm), large capillary pores (0.05-5μm) and non-capillary pores (>5μm), covering four different scale ranges. The presence of these pores has a significant impact on the various properties of cement-based materials, such as freeze-thaw cycles, carbonization, penetration, and chemical and physical effects such as steel corrosion.
[0008] In addition, different mixing ratios will also affect the pore structure of cement-based materials. By adjusting the amount of CNF and the ratio of cement, water, etc., the pore structure of cement-based materials can be optimized, thereby improving its mechanical properties and durability. Therefore, in-depth testing and analysis of the pore structure of cement-based materials is of vital importance for a deep understanding of its physical properties and analyzing the effects of different raw materials and ratios.
[0009] In conclusion, the highly reactive and well-dispersed CNF prepared by surface modification provides a new idea for improving the performance of cement-based materials. The addition of these modified CNFs can not only improve the mechanical properties and durability of cement-based materials, but also improve their working performance by optimizing the pore structure. Future research can further explore the surface modification methods of CNFs, optimize the dosage and ratio of CNFs, so as to maximize the performance of cement-based materials. At the same time, in-depth research on the interaction mechanism between CNFs and cement-based materials will help to better understand their strengthening and toughening mechanisms, and provide a theoretical basis for the development of high-performance cement-based composites. Summary of the invention
[0010] In view of this, the present invention provides a cement slurry porosity research technology using X-CT and low-field nuclear magnetic resonance. The research technology of the present invention can not only realize non-destructive three-dimensional visualization detection of the pore structure of cement slurry, but also can analyze the pore size distribution and its influence on material properties at multiple scales, and can optimize the mix ratio and microstructure design of cement-based materials, providing a theoretical basis for finding an optimal dispersion method, and ultimately achieving the purpose of improving the performance and durability of cement-based materials.
[0011] Specifically, the present invention provides a cement slurry porosity detection method, which includes the following steps.
[0012] Step 1: Provide a cement-based material test block, add nanocellulose using four different dispersion methods into the cement-based material, and cure for 7 days.
[0013] Step 2: Use X-ray computed tomography (X-CT) to perform nondestructive testing on the cement-based material test block to obtain the two-dimensional and three-dimensional distribution and morphology of the pores of the cement-based material test block after curing for 7 days, and obtain values such as pore volume, equivalent diameter, and sphericity.
[0014] Step 3: Use low-field nuclear magnetic resonance (NMR) technology to perform non-contact continuous detection on the cement-based material test block to obtain the pore volume and pore size spatial distribution of the cement-based material test block after curing for 7 days, and then obtain the total porosity.
[0015] According to the two-dimensional and three-dimensional distribution and morphology of the pores, the pore volume, equivalent diameter, sphericity and other values, as well as the total porosity can be obtained, and the test analysis from nanopores to micropores can be realized, which provides an effective multi-scale coverage, all-round display and precise visualization advanced technical means for the study of the pore structure of cement-based materials.
[0016] In some specific embodiments of the present invention, the cement-based material test block in step 1 is prepared by mixing ordinary Portland cement of P·O 42.5 grade with water at a water-cement ratio of 0.45 to prepare a cement paste; treating CNF by different dispersion methods, and directly adding CNF cement paste without dispersion process as a blank control ( WD ), high intensity ultrasonic treatment ( HU ), high-intensity ultrasound and addition of surfactant CTAB mixed treatment ( MP ). It is characterized by comprising the following steps.
[0017] WD : Enteromorpha-based CNF powder was directly mixed with cement and stirred to prepare cement slurry, and the CNF addition amount accounted for 0.05% of the cement mass.
[0018] HU : The Enteromorpha-based CNF water suspension was dispersed under a high-intensity ultrasonic probe with a power of 180 W for 30 minutes, mixed with cement to prepare cement slurry, and the CNF addition amount accounted for 0.05% of the cement mass.
[0019] MP : Use the above ultrasonic bath ( HU ) and adding surfactant CTAB to disperse the Enteromorpha-based CNF aqueous suspension. In order to eliminate the bubbles generated by CTAB, the same mass of defoamer TBP was added at the same time. The amount of CNF added accounted for 0.05% of the cement mass, and the amount of CTAB added accounted for 0.02% of the cement mass.
[0020] In some specific embodiments of the present invention, the step of using X-ray computed tomography (X-CT) to detect the cement-based material test block in step 2 to obtain the two-dimensional and three-dimensional distribution and morphology of the pores of the cement-based material test block after curing for 7 days, and to obtain the values of pore volume, equivalent diameter, sphericity, etc. specifically includes: after detecting the cement-based material test block by X-ray computed tomography, using Avizo software, using threshold segmentation, using Separate Objects method was used to obtain the two-dimensional images of cement-based material test blocks under different dispersion methods; grayscale values were derived from micro-CT images using Avizo software, and the threshold method was used to separate these phases; the grayscale pattern was modeled using a Gaussian curve; the image was segmented using the threshold segmentation method, and then pores of different sizes were rendered into different colors to obtain the distribution and morphology of the pores of the cement-based material test blocks under different dispersion methods, and the three-dimensional distribution and morphology of the pores were checked to obtain the pore volume, equivalent diameter, sphericity and other values of the cement-based material test blocks under different dispersion methods, and then the equivalent diameter was used as the independent variable and the sphericity was used as the dependent variable to draw the graph, and the relationship between the sphericity and the equivalent diameter under different dispersion methods was obtained.
[0021] In some specific embodiments of the present invention, in step 3, the step of using low-field nuclear magnetic resonance (NMR) technology to perform non-contact continuous detection on the cement-based material test block to obtain the internal pore volume and pore size spatial distribution of the cement-based material test block after 7 days of curing specifically includes: after curing the Enteromorpha-based cellulose nanofiber (CNF) cement slurry material modified based on different dispersion technologies for 7 days, using low-field nuclear magnetic resonance to detect the nuclear magnetic resonance relaxation signal of hydrogen protons in the porous structure of the cement-based material test block to obtain a relationship graph between signal intensity and relaxation time interval; analyzing the relationship graph between signal intensity and relaxation time interval to obtain the internal pore volume and pore size spatial distribution of the cement-based material test block during the curing process; and then obtaining the total porosity of the cement-based material test block after 7 days of curing.
[0022] The present invention provides a technology combining X-CT and low-field nuclear magnetic resonance, which can realize quantitative evaluation of nanoscale pore structure, accurately obtain volume information and pore size distribution characteristics of nanoscale pores, make up for the shortcomings of X-CT in nanoscale detection, and realize accurate testing in the full pore size range from gel pores to non-capillary pores.
[0023] The present invention also provides a new perspective and methodology for the scientific study of the pore structure of cement-based materials. It is expected that this method will promote the development of the field of pore structure of cement-based materials and provide strong technical support and new research directions for in-depth research in this field.
[0024] Compared with the prior art, the present invention has the following significant advantages and effects.
[0025] ①It can provide more accurate and comprehensive pore structure information of cement-based materials.
[0026] ②It can effectively evaluate the effects of different dispersion modification methods on the performance of cement-based materials.
[0027] ③It helps to develop cement-based composite materials with better performance and durability.
[0028] ④It can guide the mix design and production process optimization of cement-based materials.
[0029] ⑤It will help promote the research and development and application of high-performance cement-based materials.
[0030] In summary, the present invention provides a comprehensive, multi-scale testing and analysis method for the porosity study of cement-based materials by combining X-CT and low-field nuclear magnetic resonance technology. It can not only deeply understand the relationship between the microstructure and performance of the material, but also guide the actual material design and modification, which has important scientific significance and application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a flow chart of the testing and analysis method of the pores of cement-based materials.
[0032] Figure 2 It is the gray distribution map of micro-CT image identified by threshold segmentation method.
[0033] Figure 3 The original slice images and labeled images used for micro-CT analysis of different specimens. From left to right, the Plain , WD , HU and MP Processed CT images. a, b, c, d) are original images; e, f, g, h) are labeled images.
[0034] Figure 4 Figure 2 shows the pore size distribution (a) and pore volume fraction (b) of cement paste samples cured for 7 days by four different dispersion techniques with the addition of Enteromorpha-based CNF. DETAILED DESCRIPTION
[0035] The present invention provides a cement-based porosity testing technology using X-CT and low-field nuclear magnetic resonance, which can effectively solve the porosity problem of cement-based materials under different dispersion methods of nanocellulose, and provide a new idea for subsequent search for an optimal dispersion method. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0036] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0037] The existing technologies mostly use pressure analysis and gas phase adsorption method to test the pores of cement-based materials. The technology is relatively simple and is a destructive test, which makes it impossible to compare and link tests with similar technologies, and it is impossible to intuitively measure the influencing factors and three-dimensional distribution of the pores of cement-based materials (including nanopores and micropores). It is even more impossible to continuously test the spatiotemporal evolution of the pore structure of cement-based materials during the curing process (that is, the change process of the pore structure of cement-based materials over time). Based on this, an embodiment of the present invention provides a test and analysis method (dynamic analysis method) for the pores of cement-based materials, wherein, as Figure 1 As shown, the following steps are included.
[0038] S11: providing cement-based material test pieces, and adding nanocellulose under five different dispersion methods into the cement-based material.
[0039] S12: The cement-based material test block is tested by X-ray computed tomography to obtain the two-dimensional and three-dimensional distribution and morphology of the pores of the cement-based material test block after curing for 7 days, and the pore volume, equivalent diameter, sphericity and other values can be obtained.
[0040] The cement-based material test block is tested by low-field nuclear magnetic resonance to obtain the pore volume and pore size spatial distribution of the cement-based material test block after curing for 7 days, and then the total porosity is obtained.
[0041] S13: According to the two-dimensional and three-dimensional distribution and morphology of the pores, the values of pore volume, equivalent diameter, sphericity, and total porosity can be obtained to achieve multi-scale testing and analysis of the pores of the cement-based material.
[0042] The technical effects of the present invention are described in detail below in conjunction with this experiment.
[0043] In step S12, in some embodiments, Figure 2 As shown in the figure, the image shows the regions of interest of different samples after grayscale value transformation. In order to improve the accuracy of phase identification, Gaussian curves are used to model the grayscale pattern. The figure shows that all grayscale value curves can be accurately approximated by three Gaussian curves. The boundary separating the two phases is depicted as the intersection between the individual Gaussian curves (such as Figure 2The vertical red dashed line in the figure shows the grayscale value of the three phases. According to previous reports, Gauss-1 can be attributed to the pore / graphene oxide phase (lowest grayscale value and density), Gauss-2 comes from the hydration product (medium grayscale value and density), and Gauss-3 is attributed to the unhydrated cement particles (highest grayscale value and density). The grayscale value distribution of different phases is shown in Table 1. The grayscale value distribution of the three phases of different cement composites is also inconsistent, which may be caused by different measurement conditions of samples and CT instruments. Table 1 shows the grayscale value distribution of different phases.
[0044] Table 1 Gray value distribution diagram of different phases Dispersion method Pore / CNF Hydration products Unhytrated cement <20.64 20.64-52.80 >52.80 <22.89 22.89-52.89 >52.89 <20.19 20.19-45.37 >45.37 <19.52 19.52-46.42 >46.42
[0045] like Figure 3 As shown, the cement-based material test block is detected by X-CT to obtain the original slice images of the cement-based material test block under different dispersion methods. The obtained micro CT image has a 16-bit resolution and includes grayscale values from 0 to 65535. The distribution of these grayscale values is closely related to the density of the material. The greater the density, the higher the grayscale value, and therefore the brighter it appears on the CT image. Hardened cement paste mainly includes pores, hydration products, and unhydrated cement phases, each of which has a different physical density. This property helps to identify different phases in cement composites through micro CT imaging. The distinction between these phases can be achieved through image segmentation processing. In this study, a threshold method was used to separate these phases according to the method described in the reference.
[0046] like Figure 3 As shown in the figure, a typical slice image used for micro-CT analysis. Figure 3 As shown in a), the circular black area is the pore phase, the gray area is the hydration product, and the brighter particles are the unhydrated cement particles. Figure 3 b) shows a large number of irregular black areas. Based on previous studies, we speculate that some of these defects may be caused by the agglomeration of Enteromorpha-based CNFs, indicating that Enteromorpha-based CNFs dispersed without any dispersion technology will produce a large number of agglomerates in the cement paste, thus affecting the overall uniformity. Therefore, it is necessary to use effective technology to achieve uniform dispersion of graphene oxide. Figure 3 c, d) it can be seen that after treatment with water reducer and silane coupling agent, the aggregation of CNF based on Enteromorpha in cement slurry was significantly reduced.
[0047] like Figure 3e, f, c, d), the image is threshold segmented, and then pores of different sizes are rendered into different colors to obtain the distribution and morphology of the pores (micrometers and above) of the cement-based material test block at different curing days, and different colors represent pores of different sizes and pore positions. Then, according to the three-dimensional distribution and morphology of the pores, the total number of pores, the total porosity, the number of pores with different equivalent diameters, and the porosity of pores with different equivalent diameters of the cement-based material test block under different dispersion methods are obtained; thus providing a macroscopic basis for finding an optimal dispersion method.
[0048] In step S12, in some embodiments, the four cement-based material test blocks are tested using low-field nuclear magnetic resonance to obtain the pore volume and pore size spatial distribution of the cement-based material test blocks after curing for 7 days, and then the total porosity is obtained. The steps specifically include:
[0049] After curing for 7 days, the four cement-based material test blocks were tested using low-field nuclear magnetic resonance to obtain a relationship diagram between signal intensity and relaxation time interval.
[0050] The obtained signal intensity versus relaxation time interval graph is further analyzed in detail, as follows.
[0051] ① Data acquisition: Conduct NMR experiments and record the signal intensity at different relaxation times t I (t).
[0052] ② Fitting relaxation time distribution: Fit the signal intensity data and obtain the relaxation time distribution curve according to the following formula ) in: I 0 is the initial signal strength t is the relaxation time T 2 is the transverse relaxation time
[0053] ③Aperture distribution calculation: by measuring the signal intensity at different relaxation times t I (t), the relaxation time distribution curve can be constructed. Then the relaxation time distribution is converted to pore size distribution according to the following formula:
[0054] in: T 2 is the transverse relaxation time S / V is the specific surface area ρ is the surface relaxation rate
[0055] Through the above steps, the pore size distribution curve can be obtained to characterize the pore size distribution and pore volume fraction of the four cement-based material test blocks after curing for 7 days, as shown in FIG. Figure 4 As shown, the total porosity of the cement-based material test block after curing for 7 days was obtained.
[0056] In this embodiment, by using low-field nuclear magnetic resonance, the relationship between the pore volume and pore diameter of the cement-based material test block after 7 days of curing (nanoscale) can be obtained, which makes up for the shortcomings of X-CT detection (nanopores cannot be detected due to the influence of accuracy).
Claims
1. A method for measuring and characterizing the pore structure of cement paste based on X-CT and low-field nuclear magnetic resonance, characterized in that: The steps include: Step 1: providing a cement-based material test block, and adding nanocellulose using four different dispersion methods into the cement-based material; Step 2: non-destructively testing the cement-based material test block by X-ray computed tomography (X-CT) to obtain the two-dimensional and three-dimensional distribution and morphology of the pores of the cement-based material test block after curing for 7 days, and to obtain values such as pore volume, equivalent diameter, and sphericity; Step 3: Use low-field nuclear magnetic resonance (NMR) technology to perform non-contact continuous detection on the cement-based material test block to obtain the pore volume and pore size spatial distribution of the cement-based material test block after curing for 7 days, and then obtain the total porosity; According to the two-dimensional and three-dimensional distribution and morphology of the pores, the pore volume, equivalent diameter, sphericity and other values, as well as the total porosity can be obtained, and the test analysis from nanopores to micropores can be realized, which provides an effective multi-scale coverage, all-round display and precise visualization advanced technical means for the study of the pore structure of cement-based materials.
2. The test analysis method according to claim 1, characterized in that: The step of using X-ray computed tomography (X-CT) to detect the cement-based material test block to obtain the two-dimensional and three-dimensional distribution and morphology of the pores of the cement-based material test block after curing for 7 days, and obtaining values such as pore volume, equivalent diameter, and sphericity specifically includes: After the cement-based material test block is detected by X-ray computed tomography, two-dimensional images of the cement-based material test block under different dispersion methods are obtained by Avizo software, using threshold segmentation and Separate Objects method; Gray values were exported from the micro-CT images using Avizo software, and the threshold method was used to separate these phases; Gaussian curve is used to model the grayscale pattern; The image was segmented using the threshold segmentation method, and then pores of different sizes were rendered in different colors to obtain the distribution and morphology of the pores of the cement-based material test blocks under different dispersion methods. The three-dimensional distribution and morphology of the pores were checked to obtain the pore volume, equivalent diameter, sphericity and other values of the cement-based material test blocks under different dispersion methods. The equivalent diameter was used as the independent variable and the sphericity was used as the dependent variable to draw a graph, and the relationship between the sphericity and the equivalent diameter under different dispersion methods was obtained.
3. The test analysis method according to claim 1, characterized in that: The steps of performing non-contact continuous detection on the cement-based material test block by using low-field nuclear magnetic resonance (NMR) technology to obtain the pore volume and pore size spatial distribution inside the cement-based material test block after curing for 7 days specifically include: After curing the Enteromorpha-based cellulose nanofiber (CNF) cement slurry material modified by different dispersion technologies for 7 days, the nuclear magnetic resonance relaxation signal of hydrogen protons in the porous structure of the cement-based material test block was detected by low-field nuclear magnetic resonance, and a relationship diagram between the signal intensity and the relaxation time interval was obtained; Analyzing the relationship between the signal intensity and the relaxation time interval to obtain the pore volume and pore size spatial distribution inside the cement-based material test block during the curing process; Then, the total porosity of the cement-based material test block after curing for 7 days was obtained.
4. And then provide more accurate and comprehensive data support for finding an optimal dispersion method.
5. A method for measuring and characterizing the pore structure of cement paste based on X-CT and low-field nuclear magnetic resonance, characterized in that: The steps include: Provide cement-based material test blocks; The cement-based material test block is tested by X-ray computed tomography to obtain the two-dimensional and three-dimensional distribution and morphology of the pores of the cement-based material test block after curing for 7 days, and the values of pore volume, equivalent diameter, sphericity, etc. can be obtained; The cement-based material test block is non-contact and continuously detected by low-field nuclear magnetic resonance to obtain the pore volume and pore size spatial distribution inside the cement-based material test block after curing for 7 days, and then the total porosity is obtained; According to the two-dimensional and three-dimensional distribution and morphology of the pores, the pore volume, equivalent diameter, sphericity and other values, as well as the total porosity can be obtained, and the test analysis from nanopores to micropores can be realized, which provides an effective multi-scale coverage, all-round display and precise visualization advanced technical means for the study of the pore structure of cement-based materials.
6. The cement-based material test block according to claim 4, characterized in that: The steps include: Mix P·O 42.5 grade ordinary Portland cement with water at a water-cement ratio of 0.45 to make cement paste (hereinafter referred to as: Plain ); CNF was treated by different dispersion methods, and the CNF cement slurry without dispersion process was directly added as blank control ( WD ), high intensity ultrasonic treatment ( HU ), high-intensity ultrasound and addition of surfactant CTAB mixed treatment ( MP ). It is characterized by comprising the following steps: WD : Enteromorpha-based CNF powder was directly mixed with cement and stirred to prepare cement paste, with the CNF addition amount accounting for 0.05% of the cement mass; HU : The Enteromorpha-based CNF water suspension was dispersed under a high-intensity ultrasonic probe with a power of 180 W for 30 minutes, mixed with cement to prepare cement slurry, and the amount of CNF added accounted for 0.05% of the cement mass; MP : Use the above ultrasonic bath ( HU ) and adding surfactant CTAB to disperse the Enteromorpha-based CNF aqueous suspension. In order to eliminate the bubbles generated by CTAB, the same mass of defoamer TBP was added at the same time. The amount of CNF added accounted for 0.05% of the cement mass, and the amount of CTAB added accounted for 0.02% of the cement mass.
7. A method for measuring and characterizing the effect of different dispersion techniques on the pore structure of cement slurry materials without or with Enteromorpha-based CNF, characterized in that: The steps include: Each cement-based material test block was cured for 7 days; The cement-based material test block of claim 5 is tested by X-ray computed tomography to obtain the two-dimensional and three-dimensional distribution and morphology of the pores of the cement-based material test block during the curing process, and the values of the pore volume, equivalent diameter, sphericity, etc. can be obtained; The cement-based material test blocks according to claim 5 are tested by low-field nuclear magnetic resonance to obtain the pore volume and pore size spatial distribution of each cement-based material test block, and then the total porosity is obtained; The effects of different dispersion techniques on gel pores (0.5 - 10 nm), small capillary pores (10 - 50 nm), large capillary pores (0.05 - 5 μm), and non-capillary pores (> 5 μm) were analyzed.
8. The abbreviations in brackets above will be used later in this article.
Citation Information
Cited By
Water state evolution characterization method and device for cement hydration
CN121231529A